An innovative deterministic algorithm for optimal placement of micro phasor measurement units in radial electricity distribution systems. Issue 1 (24th December 2021) - Gholizadeh Manghutay, Aref; Salay Naderi, Mehdi; Fathi, Seyed Hamid
Abstract : Purpose: Heuristic algorithms have been widely used in different types of optimization problems. Their unique features in terms of running time and flexibility have made them superior to deterministic algorithms. To accurately compare different heuristic algorithms in solving optimization problems, the final optimal solution needs to be known. Existing deterministic methods such as Exhaustive Search and Integer Linear Programming can provide the final global optimal solution for small-scale optimization problems. However, as the system grows the number of calculations and required memory size incredibly increases, so applying existing deterministic methods is no longer possible for medium and large-scale systems. The purpose of this paper is to introduce a novel deterministic method with short running time and small memory size requirement for optimal placement of Micro Phasor Measurement Units ( µ PMUs) in radial electricity distribution systems to make the system completely observable. Design/methodology/approach: First, the principle of the method is explained and the observability of the system is analyzed. Then, the algorithm's running time and memory usage when applying on some of the modified versions of the Institute of Electrical and Electronics Engineers 123-node test feeder are obtained and compared with those of its deterministic counterparts. Findings: Because of the innovative method of step-by-step placement of µ PMUs, a unique method is developed. Simulation results elucidate that the proposed method has unique features of short running time and small memory size requirements. Originality/value: While the mathematical background of the observability study of electricity distribution systems is very well-presented in the referenced papers, the proposed step-by-step placement method of µ PMUs, which shrinks unobservable parts of the system in each step, is not discussed yet. The presented paper is directly applicable to typical problems in the field of power systems.